Molecular network-based analysis of the mechanism of liver injury induced by volatile oils from Artemisiae argyi folium - Hongjie Liu; Sha Zhan; Yan Zhang; Yan Ma; Liang Chen; Lingxiu Chen; Hanqiu Dong; Min Ma; Zhe Zhang (BMC, 2017)
Abstract Background Volatile oils from Artemisiae argyi folium (VOAAF) is reported with hepatotoxicity, but the underlying mechanism is still unclear. Methods In the present study this molecular mechanism was explored with the Ingenuity Pathway Analysis (IPA). The chemical components of the VOAAF were searched in the database, and their target proteins were all identified in the PubChem, while drug-induced liver injury (DILI) genes were searched in the PubMed gene databases. The molecular network of protein targets for VOAAF and DILI genes was built with the IPA. The canonical pathways between the 2 networks were compared to decipher the molecular mechanisms of the liver injury induced by VOAAF. Results There were 159 target proteins for VOAAF and 338 genes related to DILI identified, which were further analyzed in the IPA. The canonical pathway comparison showed that VOAAF and DILI both worked on aryl hydrocarbon receptor (AHR), lipopolysaccharide (LPS)/interleukin 1 (IL-1) mediated inhibition of retinoid X receptor (RXR) function, pregnane X receptor (PXR)/RXR activation, xenobiotic metabolism, peroxisome proliferator-activated receptor (PPAR), hepatic cholestasis, farnesoid X receptor (FXR)/RXR activation, and glucocorticoid receptor. Conclusion VOAAF-induced liver injury may be involved in many pathways in which the AHR signaling and LPS/IL-1 mediated inhibition of RXR function pathways could be the most vital.